PENERAPAN PENDEKATAN CULTURALLY RESPONSIVE TEACHING (CRT) UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF PADA MATERI BANGUN DATAR DI KELAS V SEKOLAH DASAR - Devi Kurniawati; Lilis Supratman; Nurul Fajria; Elisabeth Nova Ekasari Fallo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the improvement in cognitive learning outcomes ofstudents in flat shape material using the Culturally Responsive Teaching (CRT)approach. This study is a classroom action research (CAR) which has stages; a)Planning; b) Implementation; c) Observation; d) Reflection, with the researchsubjects being all 22 fifth grade students. Data collection in this study wasconducted using observation and tests in the form of students' cognitive learningoutcomes. The research was conducted in two cycles, with Cycle I consisting ofone meeting and Cycle II consisting of one meeting. The results of the studyshowed an increase in cognitive learning outcomes in the subject of flat shapesusing the CRT approach, as seen from the achievement of scores that met theclass completion criteria from Cycle I to Cycle II. The cognitive learning outcomesof students in the pre-cycle showed a score of 18.18%, which increased to 72.72%in Cycle I, and finally reached 86.36% in Cycle II. Based on these findings, it canbe concluded that the CRT approach is effective in improving students' cognitivelearning outcomes in flat shape material.